2005
DOI: 10.1111/j.1365-2222.2005.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal agents in house dust and wheeze in children: the PARSIFAL study

Abstract: Not only bacterial endotoxin but also mould components might offer some protection against atopic wheeze in children. However, the protective effect of being raised on a farm was largely unexplained by the mattress microbial agent levels measured in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 30 publications
(40 reference statements)
6
109
2
3
Order By: Relevance
“…Fungal EPS are stable carbohydrates secreted or shed during fungal growth and have antigenic specificity at the genus level. In contrast to the findings on visible mould, longitudinal studies have shown that exposure to (1,3)-b-D-glucan and EPS was inversely associated with the development of wheezing symptoms and reported physician-diagnosed asthma in children [8][9][10][11][12]. In addition, one case-control study reported that elevated levels of (1,3)-b-D-glucan and EPS exposure from mattress dust were associated with a lower prevalence of allergic sensitisation in 2-4-yr-old children [13].…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Fungal EPS are stable carbohydrates secreted or shed during fungal growth and have antigenic specificity at the genus level. In contrast to the findings on visible mould, longitudinal studies have shown that exposure to (1,3)-b-D-glucan and EPS was inversely associated with the development of wheezing symptoms and reported physician-diagnosed asthma in children [8][9][10][11][12]. In addition, one case-control study reported that elevated levels of (1,3)-b-D-glucan and EPS exposure from mattress dust were associated with a lower prevalence of allergic sensitisation in 2-4-yr-old children [13].…”
mentioning
confidence: 81%
“…Exposure to EPS was found to significantly reduce the risk of physician-diagnosed asthma [62] and atopic wheeze [10], while exposure to (1,3)-b-Dglucan was significantly inversely related to sensitisation against inhalant allergens among 2-4-yr-old children [13].…”
Section: Mould Components Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed reduced prevalence of allergic sensitisation and, to a lesser extent, of asthma in children exposed to farms, compared with rural peers [143,144]. Based on the hygiene hypothesis, it has been suggested that exposure to high concentrations of biological compounds in this environment could explain the observed protective effect [75,93,145].…”
Section: In Childrenmentioning
confidence: 99%
“…Ainsi, dans les pathologies respiratoires chroniques, le microbiome pulmonaire est altéré, il est dysbiotique (Figure 3). Il évoluera dans le temps en fonction de la pathologie mais, quelle qu'elle ronnement dans lequel les enfants grandissent (milieu rural versus milieu urbain), sa contamination bactérienne et fongique, et le risque de développer une atopie ou un asthme [38,39]. Par ailleurs, les infections virales, notamment les bronchiolites de l'enfance et en particulier celles à rhinovirus, semblent être impliquées dans la genèse de l'asthme, peut-être sur des terrains prédisposés [40][41][42].…”
Section: Microbiome Pulmonaire Et Asthmeunclassified